2015
DOI: 10.1007/s00709-015-0816-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Triticum aestivum seedling response to the excess of zinc

Abstract: The effects of 50 and 300 mg L−1 Zn2+ (50 Zn and 300 Zn) were investigated in Triticum aestivum (cv. Żura) grown hydroponically for 7 days. Although wheat treated with 50 Zn took up relatively high amount of the metal (8,943 and 1,503 mg kg−1 DW in roots and shoots, respectively), none of the morphological and cytological parameters were changed. After 300 Zn, the metal concentration increased to 32,205 and 5,553 mg kg−1 DW in roots and shoots, respectively. It was connected with the depletion of shoot and roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Adverse effects of metallic stress on plant morphogenesis have been demonstrated not only in the presented research, but also in other species belonging to various taxa. For example, the research of Malar et al [39] on sensitive Eichhornia crassipes specimens revealed the negative impact of Pb ions at the concentration of 100 mg L −1 on shoot and root growth, while Glińska et al [40] observed Triticum aestivum growth inhibition when 300 mg L −1 of Zn was used. Therefore, our results confirmed the sensibility of the NM ecotype, whereas the reaction of the SER one was quite interesting since SER specimens were found not to be fully adapted to the applied HMs.…”
Section: Morphogenetic Response Of Hm-treated Cultures Is Diversifiedmentioning
confidence: 99%
See 2 more Smart Citations
“…Adverse effects of metallic stress on plant morphogenesis have been demonstrated not only in the presented research, but also in other species belonging to various taxa. For example, the research of Malar et al [39] on sensitive Eichhornia crassipes specimens revealed the negative impact of Pb ions at the concentration of 100 mg L −1 on shoot and root growth, while Glińska et al [40] observed Triticum aestivum growth inhibition when 300 mg L −1 of Zn was used. Therefore, our results confirmed the sensibility of the NM ecotype, whereas the reaction of the SER one was quite interesting since SER specimens were found not to be fully adapted to the applied HMs.…”
Section: Morphogenetic Response Of Hm-treated Cultures Is Diversifiedmentioning
confidence: 99%
“…Similarly, their roles in plant cells remain still quite enigmatic, despite numerous studies being conducted. Stromules were found to be involved in facilitating the transport of macromolecules or signals such as proteins, salicylic acids, or H 2 O 2 , which must pass from one location to another [40,55,56]. In this context, stromules may reduce the diffusion distance between cell compartments that exchange substrates and products for another metabolic pathway.…”
Section: Stromules As Unique Feature Of Cal Chloroplastsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). The latter may be induced by defence mechanisms which are responsible for the Zn immobilization in vacuoles or cell walls [56][57][58][59] .…”
Section: Resultsmentioning
confidence: 99%
“…This has led to an erroneous impression in the mind of the non-specialist that mesophyll chloroplasts do not exhibit stromules while the most extensive and numerous stromules are observed in non-green plastids (Köhler and Hanson, 2000 ). Stromule formation has been observed in response to alteration in plastid redox status (Itoh et al, 2010 ; Brunkard et al, 2015 ), elevated temperatures (Holzinger et al, 2007a ), symbiotic interactions (Fester et al, 2001 ; Hans et al, 2004 ; Lohse et al, 2005 ), virus and bacterial infection (Caplan et al, 2008 ; Krenz et al, 2012 , 2014 ; Erickson et al, 2014 ) and growth regulator and mineral nutrient stress (Gray et al, 2012 ; Glińska et al, 2015 ). Stromule formation is also attributed to changes in plastid size and density within a cell (Pyke and Howells, 2002 ; Waters et al, 2004 ).…”
Section: Stroma-targeted Fps Have Led To Major Insights Concerning Thmentioning
confidence: 99%